Induction of neoplasms by subgroup E recombinants of exogenous and endogenous avian retroviruses (Rous-associated virus type 60). - Crittenden, L B (1980)
Chickens susceptible to infection with subgroup E viruses were inoculated with four independent isolates of Rous-associated virus type 60 (RAV-60) that are subgroup e recombinants of endogenous and exogenous virus. Neoplasms developed in each inoculated group. Therefore, nontransforming viruses of subgroup E can induce lymphoid leukosis at a moderate rate compared with RAV-0, a subgroup E endogenous virus, suggesting that oncogenicity is not a viral envelope (env)-related characteristic. Since the common (c) regions of the RAV-60s examined were of exogenous origin, we suggest that the c region rather than env is important for a high rate of induction of lymphoid leukosis and related neoplasms.